2003
DOI: 10.1046/j.1365-2389.2003.00517.x
|View full text |Cite
|
Sign up to set email alerts
|

Zinc ion adsorption on montmorillonite–Al hydroxide polymer systems

Abstract: Summary Clay–Al hydroxide polymers (CAlHO) can bind heavy metals effectively and may play an important role in the adsorption behaviour and metal binding capacity of soils. We studied the dependence of Al loading and pH on the adsorption of Zn on Na‐saturated montmorillonite–Al hydroxide polymer systems. The available binding sites on Al hydroxide polymers (AlHO) had a very strong affinity for Zn ions. Zinc binding on the clay surface became important when the binding sites on the AlHO were nearly all occupied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 19 publications
1
19
0
Order By: Relevance
“…Additional Zn inputs may therefore not be converted into Zn-HIM, thus favoring the formation of other Zn-species or Zn leaching to deeper soil horizons. In batch experiments, the extent of specific sorption of Zn to HIM was shown to increase with increasing pH (Lothenbach et al, 1997; Janssen et al, 2003). However, the limited number of specific sorption sites for Zn in HIM and the limited abundance of HIM in soils pose limits to the amounts of Zn that can be bound as Zn-HIM (Jacquat et al, 2009).…”
Section: Occurrence and Abundance Of Zn-himmentioning
confidence: 99%
“…Additional Zn inputs may therefore not be converted into Zn-HIM, thus favoring the formation of other Zn-species or Zn leaching to deeper soil horizons. In batch experiments, the extent of specific sorption of Zn to HIM was shown to increase with increasing pH (Lothenbach et al, 1997; Janssen et al, 2003). However, the limited number of specific sorption sites for Zn in HIM and the limited abundance of HIM in soils pose limits to the amounts of Zn that can be bound as Zn-HIM (Jacquat et al, 2009).…”
Section: Occurrence and Abundance Of Zn-himmentioning
confidence: 99%
“…Differentiation between these two trends by LCF was complicated, because they both had similar effects on the shape of the EXAFS spectra (reduced second shell and higher shell signals compared to Zn incorporated into dioctahedral vacancies). According to Janssen et al (2003b), uptake of Zn by cation exchange only becomes relevant once sorption to Al-polymers approaches its maximum.…”
Section: Sorption Of Zn In Hydroxy-interlayered Mineralsmentioning
confidence: 99%
“…The formation of hydroxy-Al interlayers in smectites or vermiculites strongly reduces the cation exchange capacity (CEC) and affects the ion sorption properties of the clay minerals (Barnhisel and Bertsch, 1989;Janssen et al, 2003b;Meunier, 2007). Laboratory studies have shown that Cu, Cd, Ni, Pb, and Zn sorb strongly to hydroxy-Al interlayered montmorillonite under acidic conditions, while 0016-7037/$ -see front matter Ó 2008 Elsevier Ltd. All rights reserved.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations